2022
DOI: 10.3390/biomedicines10071569
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Microwave Ablation Parameters for Treatment of Liver Tumors from the 3D-IRCADb-01 Database

Abstract: Simulation techniques are powerful tools for determining the optimal conditions necessary for microwave ablation to be efficient and safe for treating liver tumors. Owing to the complexity and computational resource consumption, most of the existing numerical models are two-dimensional axisymmetric models that emulate actual three-dimensional cancers and the surrounding tissue, which is often far from reality. Different tumor shapes and sizes require different input powers and ablation times to ensure the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 63 publications
(89 reference statements)
1
13
0
Order By: Relevance
“…Compared with other antenna designs (see [ 101 ] and references therein), a multi-slot coaxial antenna has a better ability to produce an optimal shape of the ablation zone pattern (see Figure 7 b) [ 101 ]. Recent simulation results have confirmed that a compact 10-slot antenna consisting of several periodic elements equivalent to a linear uniform antenna array creates near-spherical ablation zones [ 50 , 53 ]. Finely tuned impedance matching minimizes damage to the surrounding healthy tissues.…”
Section: Modeling Of the Electromagnetic Field Generated By The Antennamentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with other antenna designs (see [ 101 ] and references therein), a multi-slot coaxial antenna has a better ability to produce an optimal shape of the ablation zone pattern (see Figure 7 b) [ 101 ]. Recent simulation results have confirmed that a compact 10-slot antenna consisting of several periodic elements equivalent to a linear uniform antenna array creates near-spherical ablation zones [ 50 , 53 ]. Finely tuned impedance matching minimizes damage to the surrounding healthy tissues.…”
Section: Modeling Of the Electromagnetic Field Generated By The Antennamentioning
confidence: 99%
“…One of the most promising therapies for HCC is MWA at 2.45 GHz as a rapid treatment with a short recovery [ 9 , 113 ]. The development of mathematical models enables the determination of the optimal conditions necessary for planning patient-specific MWA procedures to be as effective as possible for treating HCC [ 50 , 53 ].…”
Section: Modeling Of Microwave Ablation In the Treatment Of Hepatocel...mentioning
confidence: 99%
See 3 more Smart Citations